A formação dos formadores: uma análise do processo formativo - Statonato, Soraia Calderoni (2010)
The aim of this work is to analyze the education process of Professores Coordenadores de Oficina Pedagógica – PCOP (Pedagogical Workshop Teacher-coordinators), who are responsible for continuing education practices within the context of one of the programs run by the state government of São Paulo: Ler e Escrever (Reading and Writing). With this aim in mind, we sought to understand how these teacher–coordinators became teacher educators, to verify what their role is, in their own perception, to identify what kind of in-service education the State Secretariat of Education offered them so that they could act as teacher educators, and learn how they feel about the whole process. The importance of this research lies on the fact that the demands of the new roles teachers are expected to play should be taken into consideration by teacher educators. An increasing number of education professionals are involved in teacher education in the state of São Paulo: Secretariat of Education technical advisors, school principals, PCOPs and teachers are all expected to take on the responsibility of teachers’ education as one of their main tasks. In order to achieve the goals of this research, five PCOPs from different Diretorias de Ensino (Regional Education Authorities) were invited to answer a questionnaire, which gave them the opportunity to discuss such issues as the relationship between being a teacher and being a teacher educator, the professional role they are now playing, the in-service education programs the State Secretariat of Education has been providing so that they can act as teachers educators themselves and their views on the whole process. Contributions from the studies of several authors - Tardif (2004, 2002, 1999), Furlanetto (2003), Pimenta (1999), Nóvoa (1992), and Gilles Ferry (1991), among others – provided the theoretical background. Data were analyzed according to the principles of qualitative investigation proposed by Bogdan and Biklen (1994). The results obtained indicate that the main motive that led PCOPs to their present post is related to professional recognition. Among their daily duties in the Oficinas Pedagógicas “Doing and Knowing” are parallel roads in their in-service education process. As to the Ler e Escrever” Program, it has been observed that a chain of ‘reproduced’ practices has been in operation: CENP (Coordenadoria de Estudos e Normas Pedagógicas) technical advisors to PCOPs, PCOPs to Professor Coordenador – PC (School Teacher Coordinator), PC to teachers. Moreover, despite the fact that PCOPs consider that the in-service education programs offered by the State Secretariat of Education provide theoretical and practical support, we believe that PCOPs’ education has contributed very little to enabling them to develop, in their work with PCs, effective actions to improve teaching and learning in schools.